Analisis Pencatatan Akuntansi Pada Usaha Mikro S3R Laundry di Kelurahan Kaluku Bodoa, Kecamatan Tallo, Kota Makassar - Nur Anita; Hariany Idris; Samsinar Samsinar (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze how accounting is carried out in the S3R Laundry micro business. This research method uses a qualitative research method, the research variable is accounting records in micro businesses and the measurement variable in this study is based on the preparation of SAK EMKM financial statements, the focus of this study is accounting records in the S3R Laundry micro business and the subject of this study is the owner of S3R Laundry, with data collection techniques through observation, interviews, and documentation. Data analysis was carried out using qualitative descriptive analysis techniques. The results of the study indicate that the financial condition of S3R Laundry in the period of March 2025 is stable and reflects fairly good business management. Based on the income statement, the total revenue earned is IDR 13,972,000 with a net profit of IDR 11,486,583. Based on the statement of financial position, total assets of IDR 57,036,583 are balanced with total liabilities and equity of IDR 57,036,583. The Notes to the financial statements explain a summary of accounting policies and the basis of measurement used in preparing the financial statements.